A noisy silence about care: Swedish preschool teachers' talk about documentation. Issue 1 (2nd January 2016) - Löfgren, Håkan
Abstract : This article investigates what happens to institutional narratives of care in Swedish preschool when a policy on increased documentation is introduced. Questions deal with preschool teachers' professionalism as expressed through the teachers' talk about documentation. The analysis is based on theories in education policy, teacher professionalism and institutional narratives. The findings show that the few references made by the teachers to narratives of care are subordinated to narratives of learning. A major conclusion is that narratives of care are in a process of becoming a 'noisy silence', which influences teachers' professionalism as well as shaping our common society.